2019
DOI: 10.1186/s40623-019-1098-3
|View full text |Cite
|
Sign up to set email alerts
|

First in-orbit results of the vector magnetic field measurement of the High Precision Magnetometer onboard the China Seismo-Electromagnetic Satellite

Abstract: The High Precision Magnetometer (HPM) is one of the main payloads onboard the China Seismo-Electromagnetic Satellite (CSES). The HPM consists of two Fluxgate Magnetometers (FGM) and the Coupled Dark State Magnetometer (CDSM), and measures the magnetic field from DC to 15 Hz. The FGMs measure the vector components of the magnetic field; while the CDSM detects the magnitude of the magnetic field with higher accuracy, which can be used to calibrate the linear parameters of the FGM. In this paper, brief descriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…On-ground prelaunch test showed that the remaining magnetic interference of the platform at the center of the CDSM sensor is lower than 0.33 nT [24]. After temperature correction, absolute value correction and elimination of platform interference, the accuracy of the magnetic field intensity observations was estimated to be within 0.5 nT [25,26].…”
Section: Magnetometers On Csesmentioning
confidence: 97%
“…On-ground prelaunch test showed that the remaining magnetic interference of the platform at the center of the CDSM sensor is lower than 0.33 nT [24]. After temperature correction, absolute value correction and elimination of platform interference, the accuracy of the magnetic field intensity observations was estimated to be within 0.5 nT [25,26].…”
Section: Magnetometers On Csesmentioning
confidence: 97%
“…(2018), B. Zhou et al. (2018, 2019), and Pollinger et al. (2020).…”
Section: The Hpm Payload and Its Calibrated Level 2 Datamentioning
confidence: 98%
“…Figure 5a shows CSES (China Seismo Electromagnetic Satellite) (Shen et al., 2018) magnetic observations (Zhou et al., 2019) along the North‐South ( B N ‐ left panel), East‐West ( B E —Central panel) and Vertical ( B C —Right panel) direction, respectively, from 11 May to 14 May 2021, after removing the internal and crustal contributions to the Earth's magnetic field by use of the CHAOS‐7 model (Finlay et al., 2020). CSES is a Chinese satellite launched on 2 February 2018, hosting a fluxgate magnetometer, two Langmuir probes, an electric field detector and two particle detectors out of eight payloads.…”
Section: Magnetospheric‐ionospheric Analysismentioning
confidence: 99%